Design of Explosive Trains of Fuzes - Grzegorz JĄCZEK; Józef GACEK; Eva FRIS (Problemy Mechatroniki)
This paper presents the examples of fuze explosive trains designing methods, on the example of 25-mm ammunition fuze. There have been described two, possible to choose, design methods for explosive trains of fuzes. The first method relies on existing solutions using the serial-produced fuzes. The second one is to develop a completely new design explosive train. This paper focuses on the second method of design of explosive trains which can be implemented in two different ways. The first way is very time consuming, long-lasting and needs an experimental work to be done. In this method, we obtained the desired result by „trial and error method”. Second method uses mutually interrelated analytical calculation methods, computer simulations, experiments, and tests. In the case of this explosive train of fuze for 25-mm ammunition, the second method for design was used. As a result of that, the operating principle of explosive train of this fuze and subsequent stages of work on its components was described. The results of experimental tests and live tests on proving ground with the use of 25-mm ammunition was described as well.